Malignant tumors in osteoarchaeological samples from Hungary - Molnár, Erika (Acta Biologica Szegediensis, 2009)
According to our current knowledge, tumors are the same age as mankind itself. The prevalence of tumorous diseases, however, was seemingly relatively low in the past and apparently increased dramatically in modern times. This theory is based on scattered case studies. However, the majority of these investigations were not carried out using modern diagnostic techniques. The scarcity of data concerning the antiquity of cancer demands new investigations in this field. Future paleopathological discoveries and the application of improved diagnostic techniques may enable „paleo-oncology” to make further contributions to our understanding of cancer. In this study, we present data on the occurrence of malignant bone tumors in 12 anthropological series (3967 individuals) from Hungary dated to the 3rd -16th centuries AD. All skeletons were subjected to a careful macroscopic investigation, complemented by radiological examination and in special case scanning electron-microscopic and histological analyses, too. We identified 13 cases of malignant bone tumors. In most instances, multiple osteolytic lesions with slight osteoblastic reactions, in characteristic skeletal distributions, were strongly suggestive of metastatic carcinoma. However, in some cases multiple myeloma cannot be excluded. A mature male with pronounced osteoblastic reactions, particularly on the hip bones, seemed to be most compatible with the diagnosis metastatic prostate cancer. These observations indicate that carcinomas were present in human populations living on the territory of present-day Hungary over the last two millennia.